Thirteen Fundamental Psychological Needs - Desmet, Pieter M.A (2020)
Although individuals may have different goals and wishes on the surface, deep down we all want the same things. Our fundamental needs are universal: Regardless of culture, age, and lifestyle, everyone ultimately has the same set of needs. Needs are the basic requirements for our functioning and the nutriments for our well-being and advancement. We can only fully develop and flourish if all our basic needs are satisfied (at least to some degree), and none can be neglected without significant negative consequences. Needs are also a strong direct source of meaning and pleasure (and displeasure): events and activities that fulfil our needs are both meaningful and pleasurable. Needs and design If one thing can be said about design, it is that its relevance to the individual and to humanity at large-its purpose, meaning, success or failure-depends on the extent to which it satisfies people's needs. Needs are the fundament of our motivation system, and all human activity is essentially fueled by the aspiration of need fulfilment. Products, systems, buildings, technology, and all other 'artificial' phenomena envisioned and built by people are essentially instruments for need satisfaction. 13 fundamental needs This booklet provides a typology of 13 fundamental psychological needs developed by Desmet and Fokkinga (2020). Each page shows a need and four corresponding sub-needs. These sub-needs illustrate the range and scope of the fundamental needs. Even though they are themselves not fundamental, they still represent relatively universal and general concepts. The (sub-) needs can, in turn, take shape as and through goals and desires that are specific to particular individuals and/or situations. You can use the overview as a source of design inspiration or, if you like, as a means to explore your personal happiness.